Determinant of Accounting Students Detecting Fraud Ability - Annafi, Reghina Azti; Bawono, Icuk Rangga; Maghfiroh, Siti (Department of Accounting, Faculty of Economics, Universitas Negeri Semarang, 2021)
This study aims to examine and analyze the influence of competence, skepticism, personality types, and gender on the ability of accounting students to detect fraud. Accounting students in this study serve as a surrogate from auditors. The amount of the sample in this study is 157 Accounting Students at Jenderal Soedirman University who were in semester VII, IX and XI. The sampling technique used in this study was purposive sampling. The data obtained were analyzed using multiple linear regression analysis techniques. The results in this study indicate that: (1) Competence has influence on the ability of accounting students to detect fraud; (2) Skepticism has influences on the ability of accounting students to detect fraud; (3) The type of personality that comes from the combination of ST and NT has influence on the ability of accounting students to detect fraud; and (4) Gender has no influence on the ability of accounting students to detect fraud. This research implies that auditors need to consider and pay attention to the competence, skepticism, and personality type possessed by someone at the time of recruitment without differentiating their gender. While academics should pay more attention and improve their competence and skepticism through both formal and non-formal education, such as attending the training.